If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w(w + 2) = 0 Reorder the terms: 2w(2 + w) = 0 (2 * 2w + w * 2w) = 0 (4w + 2w2) = 0 Solving 4w + 2w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '2w'. 2w(2 + w) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0Subproblem 2
Set the factor '(2 + w)' equal to zero and attempt to solve: Simplifying 2 + w = 0 Solving 2 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + w = 0 + -2 w = 0 + -2 Combine like terms: 0 + -2 = -2 w = -2 Simplifying w = -2Solution
w = {0, -2}
| 8(p-1.25)=4(2p-0.5) | | 105x^2-238x+105=0 | | x+0.5=-0.16666 | | 5+r/(-2)=-6 | | 14y^2=180 | | (2x^-3y^2)^-4/(2x^2y)^-3 | | y=-4x/1 | | y=4x/1 | | 3log(2x)+4=7 | | x^3+11x^2+18=0 | | 6n+21=57 | | sin^2x-3sinx-10=0 | | ln(9x-8)=6 | | 7x-4+6x=7x+35-7x | | 13(t-5)+5t=6(3t+3)-13 | | 36u^2=9u | | -6X+13+7X=-2 | | -.45(40)+.8X=.3(40+X) | | 2(-10)+5y=10 | | 4w+3w-6w-6w=w+15+2w-31 | | 1-5x=13+x | | 4g^2+2g+3=0 | | 4X+8-3X=3 | | 2y+6=8+3y | | (x-2)(3x+5)= | | -10/x=5/x-10/3 | | x-255=443 | | 46=3u-11 | | 600=2500(X)(4) | | (5x-2)/2x-18 | | 4n-6.4=2(n+1.3) | | (5x-2)/2x-18=0 |